Tradycja bizantyjska i jej wpływ na kulturę rosyjską w myśli Konstantina Leontjewa - Bala, Maciej (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The present article amounts to an attempt to analyze the Byzantine tradition in the work Byzantinism and the Slavs by Konstantin Leontiev. The thinker finds the heritage of Eastern Christianity an immanent part of the Russian national identity. Moreover, the philosopher defines Byzantinism as a type of culture with centralized power in the hands of the Romanovs. Consequently, Leontiev depicts particular stages of the evolution of this power model in Russia. The author of the paper concludes that the thinker’s considerations are centered on the emphasis on the role of monarchy in contemporary Russia rather than on its Byzantine roots.